2013
DOI: 10.1128/iai.00533-13
|View full text |Cite
|
Sign up to set email alerts
|

Requirement and Redundancy of the Src Family Kinases Fyn and Lyn in Perforin-Dependent Killing of Cryptococcus neoformans by NK Cells

Abstract: Natural killer (NK) cells directly recognize and kill fungi, such as the pathogenic fungus Cryptococcus neoformans, via cytolytic mechanisms. However, the precise signaling pathways governing this NK cell microbicidal activity and the implications for fungal recognition are still unknown. Previously, it was reported that NK cell anticryptococcal activity is mediated through a conserved phosphatidylinositol 3-kinase-extracellular signal-regulated kinase 1/2 (PI3K-ERK1/2) pathway. Using YT (a human NK-like cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 68 publications
1
27
0
Order By: Relevance
“…We also investigated PLC␥ by pretreating YT cells with the PLC␥ inhibitor, U-73122, at concentrations found to inhibit tumor killing (34). The anti-cryptococcal activity was examined, and we found that the addition of YT cells significantly reduced the number of cryptococcal cfu, which is consistent with our previous observations of killing (1,27,35). Despite using concentrations of U-73122 in excess to inhibit PLC␥, there was no impact on YT anti-cryptococcal killing, suggesting that PLC␥ was not involved in NK cell-mediated cryptococcal killing (Fig.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…We also investigated PLC␥ by pretreating YT cells with the PLC␥ inhibitor, U-73122, at concentrations found to inhibit tumor killing (34). The anti-cryptococcal activity was examined, and we found that the addition of YT cells significantly reduced the number of cryptococcal cfu, which is consistent with our previous observations of killing (1,27,35). Despite using concentrations of U-73122 in excess to inhibit PLC␥, there was no impact on YT anti-cryptococcal killing, suggesting that PLC␥ was not involved in NK cell-mediated cryptococcal killing (Fig.…”
Section: Resultssupporting
confidence: 84%
“…We found that the addition of YT cells to C. neoformans cultures reduced the number of cfu for both strain B3501 (Fig. 1, F and G) and strain 145 (data not shown), demonstrating NK cell killing of Crypto- coccus (1,24,27) and demonstrating that the vehicle control did not affect this activity. Treatment of YT cells with EHT1864 or Rac inhibitor II caused a dose-dependent increase in cfu compared with vehicle controls, indicating a loss of anti-cryptococcal activity (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Furthermore, NO production by STAT1-mediated M1 macrophages is critical for control of the intracellular growth of C. neoformans. Even in the presence of other immune cells with demonstrated anticryptococcal activity, including DCs, neutrophils, and NK cells (61,63,64,76,77), the loss of macrophages capable of polarizing to an M1 phenotype is crippling to the host's ability to mount protective responses. We definitively show that STAT1-mediated M1 macrophage activation is crucial to anticryptococcal responses, providing an effector cell population and mechanism by which the host executes protective responses against C. neoformans.…”
Section: Discussionmentioning
confidence: 99%